Response of Azadirachta Indica and Eucalyptus tereticornis to Bioinoculants (VAM, Phosphobacterium and Azospirillum) in sewage sludge amended soil - S., Mohamed Ismail; M., Subaschanrabose; S., Balasubramanian (Universiti Putra Malaysia Press, 2001)
Pot culture experiment was conducted in red loamy soil to evaluate the growth response and nutrient uptake of Azadirachta indica and Eucalyptus tereticornis grown in non-amended and sludge amended soil. Sludge application enhanced growth and biomass production of A. indica compared to E. tereticornis. Combined inoculants resulted in a significant increase in plant growth and nutrient uptake. Inoculant effectiveness was higher in tree species grown in sludge-amended soil. The present experiment clearly indicates the feasibility of using inoculation as suitable for conventional fertilizers in the establishment of forest trees.